Cobertura verde: estudo de caso no município de São José dos Campos - SP - Oliveira Neto, Adalberto Ciro de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Guided by the concepts of bioclimatic architecture and wide range of benefits , the green roof stands out as one of the ecological techniques indicated to minimize weather disturbances arising from urbanization. However, little is known what are the reasons that are preventing its spread between the construction methods. To try to understand this unfavorable scenario , we collected technical , historical and urban information of São José dos Campos, where we attempted to analyze the potential of green roof as a tool against the negative effects of heat island

Orientada pelos conceitos da arquitetura bioclimática e com vasta gama de benefícios, a cobertura verde se destaca como uma das técnicas ecológicas indicadas para minimizar os distúrbios climáticos decorrentes da urbanização. Todavia, pouco se sabe quais são os motivos que estão impedindo a sua disseminação entre os métodos construtivos. Para tentar compreender esse cenário desfavorável, foram coletados informações técnicas, históricas e urbanas do município de São José dos Campos, onde buscou-se analisar a potencialidade da cobertura verde como instrumento no combate do efeitos negativos da ilha de calor
Keywords: Urbanização; Mudanças climáticas; Arquitetura e clima; Ilha de calor urbana; Sustentabilidade; Urbanization